OPTIMALISASI MANAJEMEN ZAKAT PRODUKTIF DI ERA DIGITAL : KECAMATAN SUMBERBARU - Muhammad Husen; Mochammad Hesan ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2026)
This article aims to analyze the optimization of productive zakat management in the digital age in Sumberbaru Subdistrict by positioning the community as the subject of empowerment. The study employs a qualitative approach using a case study design combined with Asset-Based Community Development (ABCD). Data were collected through semi-structured interviews, participatory observation, and documentation involving zakat administrators, mustahik, muzaki, community leaders, and relevant stakeholders. Data analysis was conducted interactively through data condensation, data presentation, and the drawing and verification of conclusions. The ABCD approach is used to identify and mobilize individual, social, institutional, economic, physical, and digital assets available in the community to support the development of productive zakat. The study focuses on the fund management process, targeting accuracy, support for mustahik, utilization of local assets, use of digital technology, and the sustainability of empowerment programs. This study is expected to demonstrate that the optimization of productive zakat is determined not only by increased fund collection, but also by the quality of governance, the capacity of administrators, community involvement, the utilization of local potential, and the ability to adapt to digital transformation